2023
DOI: 10.3390/polym15214320
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Acrylate Oligomer (PUA) Microspheres Prepared Using the Pickering Method for Reinforcing the Mechanical and Thermal Properties of 3D Printing Resin

Xiaoliang Zhao,
Hua Jiao,
Bin Du
et al.

Abstract: Some photosensitive resins have poor mechanical properties after 3D printing. To overcome these limitations, a polyurethane acrylate oligomer (PUA) microsphere was prepared using the Pickering emulsion template method and ultraviolet (UV) curing technology in this paper. The prepared PUA microspheres were added to PUA-1,6-hexanediol diacrylate (HDDA) photosensitive resin system for digital light processing (DLP) 3D printing technology. The preparation process of PUA microspheres was discussed based on micromor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Ultraviolet (UV)-cured PU coatings have excellent characteristics such as fast curing speed, environmentally friendly, high hardness, high transparency, etc. [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Due to the low molecular weight of the UV-curing monomers used, UV-cured PU coatings have higher crosslinking density and also have the potential to be applied in the CWA resistance coating.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet (UV)-cured PU coatings have excellent characteristics such as fast curing speed, environmentally friendly, high hardness, high transparency, etc. [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Due to the low molecular weight of the UV-curing monomers used, UV-cured PU coatings have higher crosslinking density and also have the potential to be applied in the CWA resistance coating.…”
Section: Introductionmentioning
confidence: 99%
“…In a later study [30], they studied the properties of PUDs made with blends of polypropylene glycol and polycarbonate diol and found that they showed improved thermal stability. On the other hand, some literature has shown the relevance of the composition of the soft segments to the structure and performance of PUs [31][32][33].…”
Section: Introductionmentioning
confidence: 99%